A reproducible protocol for raising clonal plants from leaf segments excised from mature trees of Betula utilis a threatened tree species of Kashmir Himalayas - and Zahoor A. Kaloo1, *Mehbooba Zaki1, Mohammad Shafi Sofi2 (International Multidisciplinary Research Journal, 2011)
Tissue culture techniques such as micropropagation provide a fast and dependable method for production of a large number of uniform plantlets in a short time and offer potential means not only for rapid mass multiplication of existing stocks but also for the conservation of important, elite and rare plants. In this study, callusing was achieved from leaf explants of Betula utilis on MS medium supplemented with 2, 4-D (2.5mg/l). The callus was friable, nodular, having numerous embryoids which exhibited organogenesis on subculturing. Production of multiple shoots was achieved on MS medium supplemented with BAP (1.5mg/l). Rooting from these shoots was obtained within 10 days of inoculation on MS medium fortified with NAA (1.0mg/l). A combination of BAP (2.0mg/l) + NAA (0.5mg/l) proved to be the best auxin-cytokinin combination in which explants exhibited best morphogenetic potential in terms of development of shoots along with roots within 8-10 days of inoculation. The maximum frequency of root differentiation (8.2) roots was achieved on MS basal medium supplemented with NAA (1.0mg/l) after 10 days of inoculations in 80% cultures. The complete plantlets were produced which showed enhanced growth after transferring in the same media composition.